The 2018 assisi think tank meeting on breast cancer: International expert panel white paper. (July 2020) - Arenas, Meritxell; Selek, Ugur; Kaidar-Person, Orit; Perrucci, Elisabetta; Montero Luis, Angel; Boersma, Liesbeth; Coles, Charlotte; Offersen, Birgitte; Meattini, Icro; Bölükbaşı, Yasemin; Leonardi, Maria Cristina; Pfeffer, Raphael; et al.
Graphical abstract: Highlights: PMRT may be avoided after PST in some patients with complete pathological response. When PST transforms cN1 disease to SLN negative, axillary treatment must be defined. Hypofractionation is an option in patients with immediate breast reconstruction. Whole breast irradiation can be omitted in selected DCIS patients. Therapy de-escalation is advisable in low-risk early-stage breast cancer patients. Abstract: We report on the second Assisi Think Tank Meeting (ATTM) on breast cancer which was held under the auspices of the European Society for RadioTherapy & Oncology (ESTRO). In discussing in-depth current evidence and practice it was designed to identify grey areas in diverse forms of the disease. It aimed at addressing uncertainties and proposing future trials to improve patient care. Before the meeting, three key topics were selected: 1) primary systemic therapy, mastectomy, breast reconstruction and post-mastectomy radiation therapy, 2) therapeutic options in ductal carcinoma in situ, and 3) therapy de-escalation in early stage breast cancer. Clinical practice in these areas was investigated by means of an online questionnaire. The time lapse period between the survey and the meeting was used to review the literature and on-going clinical trials. At the ATTM both were discussed in depth and research protocols were proposed.